1992
DOI: 10.1212/wnl.42.3.614
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis in Behçet's disease

Abstract: Among 250 patients with Behcet's disease, we describe 25 cases of angiographically proven cerebral venous thrombosis. Intracranial hypertension was the most frequent manifestation. Two initially untreated patients relapsed. Treatment of cerebral venous thrombosis consisted of combined heparin and steroids in 19 patients, steroids alone in three, and heparin alone in three others. Neurologic symptoms improved rapidly in all. Nineteen patients received long-term anticoagulation, and two received aspirin. Relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1
10

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(95 citation statements)
references
References 0 publications
6
78
1
10
Order By: Relevance
“…Since the first description of neurologic involvement in BD in 1941 (18), only single cases and small series of CVT in Saadoun et al patients with BD have been reported (7)(8)(9)(10)(11)(12)(13). Certain features of the disease have been hinted at in most of these reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first description of neurologic involvement in BD in 1941 (18), only single cases and small series of CVT in Saadoun et al patients with BD have been reported (7)(8)(9)(10)(11)(12)(13). Certain features of the disease have been hinted at in most of these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term followup has not been available in most reports. Treatment for dural venous sinus thrombosis involves anticoagulation, and some authors advocate the concurrent use of corticosteroids (3,13,22) and/or immunosuppressants (23) in patients with BD. In the present study, most of the patients rapidly improved following anticoagulation without severe hemorrhagic complications, underscoring the beneficial effect of such therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arteries are less commonly involved. Seizures may occur owing to central venous thrombosis, but haemorrhage is uncommon [146].…”
Section: Behçet's Disease (Bd)mentioning
confidence: 99%
“…La utilización a largo plazo de corticoides y anticoagulantes se ha demostrado útil para el tratamiento y prevención de las trombosis venosas cerebrales en la EB (22).…”
Section: Manifestaciones Vascularesunclassified